Improving the stability and activity of oral therapeutic enzymes - Recent advances and perspectives - Fuhrmann, Gregor; Leroux, Jean-Christophe (Pharmaceutical Research, 2014)
Exogenous, orally-administered enzymes are currently in clinical use or under development for the treatment of pathologies, such as celiac disease and phenylketonuria. However, the administration of therapeutic enzymes via the oral route remains challenging due to potential inactivation of these fragile macromolecular entities in the harsh environment of the gastrointestinal tract. Enzymes are particularly sensitive because both proteolysis and unfolding can lead to their inactivation. Current efforts to overcome these shortcomings involve the application of gastro-resistant delivery systems and the modification of enzyme structures by polymer conjugation or protein engineering. This perspective manuscript reviews and critically discusses recent progress in the oral delivery of therapeutic enzymes, whose substrate is localized in the gastrointestinal tract. © 2013 Springer Science+Business Media New York.
CRIS-Team Scopus Importer:2021-06-29
Keywords: celiac disease; drug therapy; pancreas; PEG